2022
DOI: 10.5114/pm.2022.116437
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lifestyle and diet on endometriosis: a fresh look to a busy corner

Abstract: Endometriosis is a chronic inflammatory disorder with a prevalence of six to ten percent in women of childbearing age. As long as the aetiology of endometriosis is not fully understood and the disease has no definitive treatment, an examination of the environmental factors or interventions that could modify or cure endometriosis would greatly benefit women suffering from this chronic condition. This literature review utilized the electronic databases PubMed, EMBASE, and MEDLINE until February 2021. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 123 publications
0
23
0
4
Order By: Relevance
“…Besides, lifestyle and diet may affect symptoms, too. 25 The broad spectrum of PTs detected in this study may result from individual variation in ER-alpha and PR distributions. 26 It is reported that for patients with endometriosis who are intolerant of COC or norethisterone acetate’s side effects, shifting one to the other could improve their satisfaction.…”
Section: Discussionmentioning
confidence: 74%
“…Besides, lifestyle and diet may affect symptoms, too. 25 The broad spectrum of PTs detected in this study may result from individual variation in ER-alpha and PR distributions. 26 It is reported that for patients with endometriosis who are intolerant of COC or norethisterone acetate’s side effects, shifting one to the other could improve their satisfaction.…”
Section: Discussionmentioning
confidence: 74%
“…Information on imaging and physician impression of the masses was also not recorded frequently 10.3389/fmed.2023.1102437 enough to allow meaningful stratification on other diagnostic factors and this may hide interesting interactions in the data. Even though the study did not collect specific information of benign masses, the performance of OvaWatch might support the evaluation of adnexal mass suspicious as endometriosis cysts versus a mass arising from an endometrioid ovarian cancer or metastatic endometrial cancer to the ovary (32,(35)(36)(37)(38)(39) through the testing result of low probability of malignancy versus indeterminate.…”
Section: Discussionmentioning
confidence: 99%
“…This mouse model may also be useful in optimizing health care methods during the long preconception period. Although there are several epidemiological studies on the effects of lifestyle factors such as exercise and weight restriction [ 43 ], and diet factors such as high-fat diets and phytoestrogens on endometriosis, few animal studies have been reported [ 8 ]. Supplementation with inositol and melatonin, for example, has been reported to contribute to the normalization of glucose tolerance during pregnancy and is expected to positively impact fetal outcomes [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%